GENETIC ANALYSIS OF SOME SPECIES OFPinanga (PALMAE) BY USING ISSR MARKERS - Witono, Joko Ridho; Rondo, Katsuhiko (BERITA BIOLOGI, 2006)
A genetic analysis of 13 species of Pinanga (Palmae) was conducted by using Inter Simple Sequence Repeat (ISSR) markers. The markers were used in this study belonged to UBC primer set #9 (UBC 801-900) and each primer contains 15 to 22 mer nucleotides.Based on primer screening, nine UBC primers had clear and reproducible polymorphism bands. According to Dices and Jaccards similarity coefficients, cluster analysis by UPGMA among the 13 Pinanga species showed two clusters. Cluster A consisted of nine species: P. javana, P. arinasae, P. patula, P. salicifolia, P. coronata, P. scortechini, P. disticha, P. grandis and P. densiflora; and cluster B consisted of four species from five accessions: P. caesia, P. copelandi, P. rumphiana-1, P. rumphiana-2 and P. insignis. The genetic similarity among the 13 species of Pinanga had a correlation with their geographical distribution. In cluster A, all of the accessions are from Sundaland and the adjacent region of Thailand, whereas all of the accessions in cluster B were distributed in the Philippines, Wallacea, and the New Guinea regions. Possibly this genetic similarity was caused by their geographical history and the natural barriers between them. This is the early conclusion was conducted using genetic markers on Pinanga. Further studies such as sequencing (plastid and nuclear ribosomal DNA) and applying more accessions of Pinanga species from broader geographic distributions may provide a better understanding of the relationships. The 1SSR markers application is a simple and quick way to analyze genetic relationships because no prior sequence data is needed, a large number of markers can be generated, and the supplies and equipment required are minimal.